Development status of Anti-corrosion Technology for Power Transmission Tower's Steel Structure. Issue 5 (July 2020) - Li, Xinmei; Zhang, Zhongwen; Du, Baoslmai; Li, Wen; Suo, Shuai
Abstract: Higher requirements have been brought forward on the reliability and service life of power transmission tower's steel structure along with the growing of power generation capacity. This paper analyzes types of corrosion of power transmission tower's steel structure and the status of research on corrosion and summarizes categories of protective coating for steel and iron materials. Hot-dip galvanizing still remains as the main anti-corrosion method for power transmission tower's steel structure in China, while the promotion and application of cold spray technology, cold zinc-spraying anti-corrosion technology and weathering resistant steel provide more options of anti-corrosion technologies for power transmission tower. The engineering practice proves that cold zinc-spraying anti-corrosion technology has achieved superior application effects in on-site reinforcement and repair of power transmission tower.